Entrepreneurial orientation, solidarity, business strategy and firm performance of SMEs in Muara Enim, Indonesia - Sagita, Ardio (2018)
The purpose of this study was to examine the relationship of entrepreneurial orientation, solidarity, business strategy and firm performance in SMEs Muara Enim, Indonesia. The respondents of this study were SMEs owners that operating in Muara Enim, Indonesia. The factors investigated in this study were entrepreneurial orientation, solidarity and business strategy. Thus, the objectives of this research research were: (a) to examine the relationship between entrepreneurial orientation and firm performance of SMEs in Muara Enim, Indonesia (b) to exemine the relationship between solidarity and firm performance of SMEs in Muara Enim, Indonesia. (c) to examine the relationship between business strategy and firm performance of SMEs in Muara Enim, Indonesia. In this study, the quantitative method was implemented. 50 SMEs operating in Muara Enim and 44 SMEs used as the sample size. In assessing the relationship between variables, a total of 44 questionnaires were distributed and analyzed using SPSS 24.0 to produce accurate findings. Correlation and regression analysis was used to answer the research hypothesis. The finding of this research showed that entrepreneurial orientation and business strategy are significantly related to firm performance. The study clearly showed that the SMEs owners need entrepreneurial orientation and business strategy to strengthen and enhance the business performance that could lead the continuity of business. This study also contributes to new scope of research in the business field. This study also opens a new sight to SMEs owners to have further understanding on the influence of entrepreneurial orientation, solidarity and business strategy toward firm performance. This study also discusses the implications, recommendations for future research and summary of the study as well.